Kemandirian Anak Usia Dini Dengan Pola Asuh Orang Tua Single Parent yang Demokratis - Melda Hasanah; Daeng Ayub; Ria Rizkia Alvi (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Independence is an important thing that needs to be instilled in children from an early age. With children who are accustomed to being independent since childhood, they will carry over into adulthood. Independence in children can be influenced by parenting applied by parents. Single parents have multiple roles that make it difficult to share time with their children. With the use of inappropriate parenting by single parents, it can lead to less than optimal independence in children. This study aims to describe the independence of early childhood with democratic single parent parenting. This study uses a qualitative approach, which was carried out in Segati Village with 3 single mothers with 5 year old children as informants. This research data collection using documentation, observation and interviews. Data analysis with the stages of reduction, presentation and conclusion. The results showed that single parent parents who have multiple roles by applying democratic parenting can instill independence in children from a young age more optimally. Keywords: Independence, children, democratic parenting, single parent